2000
DOI: 10.1021/jp003040y
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for Computational Studies of Quininoidal Diiminediyls:  Biradical vs Dinitrene Behavior

Abstract: Density functional and post Hartree-Fock ab initio computations were carried out on the lowest singlet, triplet, and quintet states of 1,4-phenylenedinitrene, biphenyl-4,4′-dinitrene, (E)-stilbene-4,4′-dinitrene, and (E,E)-1,4-bis(4-nitrenophenyl)-1,3-butadiene, and (E,E,E)-1,6-bis(4-nitrenophenyl)-1,3,5-hexatriene. Neardegenerate singlet and triplet quinonoidal ground states were found for all systems using CASSCF methodology, with a slight favoring of the singlet, in accord with experimental results. The aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…The decrease of J as a function of the conjugated-bridge length has been theoretically evidenced, using UDFT calculations in nytronil nitroxide diradicals [12] and dinitrenes [13]. In recent experimental and theoretical studies [14,15] performed on dinuclear copper(II) complexes connected through oligoacenebis(oxamate) or oligo-paraphenylenediamine bridging ligands, Unrestricted Density Fonctional Theory (UDFT) calculations support the occurrence of a spin polarization mechanism for the exchange interaction between the two distant unpaired electrons.…”
Section: Introductionmentioning
confidence: 92%
“…The decrease of J as a function of the conjugated-bridge length has been theoretically evidenced, using UDFT calculations in nytronil nitroxide diradicals [12] and dinitrenes [13]. In recent experimental and theoretical studies [14,15] performed on dinuclear copper(II) complexes connected through oligoacenebis(oxamate) or oligo-paraphenylenediamine bridging ligands, Unrestricted Density Fonctional Theory (UDFT) calculations support the occurrence of a spin polarization mechanism for the exchange interaction between the two distant unpaired electrons.…”
Section: Introductionmentioning
confidence: 92%
“…(1 a) state (S = 0), a symmetry-breaking approach [43] within DFT was appropriate and has been widely used for such systems. [5,44] Therefore, the calculations of the ground-state singlet states were performed using either spin-restricted-or spin-unrestricted approaches (in G03, combined with GUESS = MIX).…”
Section: Physical Measurementsmentioning
confidence: 99%
“…In a series of papers, Nakano et al have evidenced on a novel structure‐property relationship between the second hyperpolarizability and the diradical character for some OS singlet polyaromatic hydrocarbons (PAHs) . Various control schemes of spin multiplicity and OS character are experimentally obtained in diradicals and multiradicals . Kubo et al and Champagne and his co‐workers quite recently succeeded in designing and synthesizing two types of relatively stable PAHs with pronounced OS singlet character.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Various control schemes of spin multiplicity and OS character are experimentally obtained in diradicals and multiradicals. [1,[6][7][8][9][10][11][12] Kubo et al [10] and Champagne and his co-workers [11] quite recently succeeded in designing and synthesizing two types of relatively stable PAHs with pronounced OS singlet character. In the solid state, recent studies have demonstrated the coexistence of intramolecular and intermolecular covalent bonds originating from the OS character of the constituent molecules.…”
mentioning
confidence: 99%